Prolactin Supplementation to Culture Medium Improves Beta-Cell Survival - Yamamoto, Toshiyuki (2010)
OBJECTIVES: Recent studies demonstrated that prolactin has beneficial effects on β-cells for islet transplantation. We examined the effect of human recombinant prolactin (rhPRL) supplementation to the culture media to determine its potential use in the context of clinical islet transplantation. MATERIALS AND METHODS: Each human islet isolated from 14 deceased multi-organ donors was cultured in Miami modified media-1 supplemented with or without rhPRL (500μg/L) for 48 hours. β-cell survival and proliferation (BrdU and Ki-67) were determined by laser-scanning cytometry. The cytoprotective effects of rhPRL against noxious stimuli were assessed by flow cytometry (tetramethylrhodamine ethyl ester). Cytokine/chemokine and tissue factor (TF) production were measured in vitro and islet potency was assessed in vivo into diabetic immunodeficient mice. RESULTS: β-cell survival during culture was 37% higher in the rhPRL group than in control (p=0.029). rhPRL protected β-cells in vitro from cytokines, Nitric Oxide donor and H(2)O(2). The exposure to rhPRL did not affect human beta-cell proliferation with our protocol. rhPRL treatment did not alter cytokine/chemokine and TF production in vitro nor affected human islet functionality in vivo: recipient mice achieved normoglycemia with a comparable tempo, while loss of graft function was observed in 2/7 mice in the control group and in none of the rhPRL group (p=n.s.). CONCLUSION: rhPRL supplementation to islet culture media improved human β-cell-specific survival without altering islet quality. Addition of rhPRL to cultured islets may grant a more viable β-cell mass in culture. The development of β-cell cytoprotective strategies will be of assistance in improving islet transplantation outcomes.